Non-linear fire analysis of restrained curved RC beams. (1st February 2015) - Ružić, D.; Kolšek, J.; Planinc, I.; Saje, M.; Hozjan, T.
Highlights: A novel, strain-based finite element formulation of the curved planar (RC) beams. Moisture and heat transfer in concrete. Consideration of stress, temperature, creep and transient strains. Effect of soil, boundary conditions on stability of RC arch is investigated. Abstract: A new finite element model for the analysis of the restrained curved reinforced-concrete (RC) beams simultaneously exposed to mechanical and extreme fire-like thermal loading is presented. The moisture and heat transfer through concrete is considered to be uncoupled with the deformation and the shape change of the beam. The hygro–thermo-mechanical analysis is performed in two separate steps, the first one starting with the coupled moisture and heat transfer analysis, and the next one continuing with the mechanical stress–strain analysis. A novel, strain-based finite element formulation of the curved planar beam has been developed for the mechanical part of the fire analysis. The unilateral soil–concrete beam contact is modelled with the set of discrete non-linear springs situated at nodes of the finite element mesh at the soil–beam contact. The model is verified by the numerical results of a full three-dimensional solid finite element model created in the LUSAS finite element analysis software and they are in good agreement with the present solution. In the subsequent parametric studies, the effects of material parameters of soil dictating the unilateral restraining forces to the beam, the load magnitude and the boundary conditions on the behaviour of the curved reinforced-concrete RC beam exposed to fire are investigated.